Update on the combination of myo-inositol/d-chiro-inositol for the treatment of polycystic ovary syndrome - Iñaki Lete; Ainara Martínez; Irene Lasaga; Eva Centurión; Amaia Vesga (Gynecological Endocrinology, 2024)
In this article, we present a narrative review on the use of inositol in the treatment of polycystic ovary syndrome (PCOS). Of the different inositols that exist, only myo-inositol (MYO) and D-chiro inositol (DCI) have been studied in the treatment of PCOS. The results of the studies show that there is insufficient or controversial evidence to recommend the use of DCI alone, while MYO alone shows positive results and, above all, the MYO/DCI combination is effective when used at a ratio of at least 40:1, but there is enough rationale to further study ratios such as 66:1 to 100:1 as other possible effective combinations.